A New Design Method for Generating Surrogate Kinematic Truss Orthoses to support Pathological Gait Patterns in Human Model Simulations - Steck, Patrick; Scherb, David; Mayer, Johannes; Jäger, Michael; Miehling, Jörg; Völkl, Harald; Wartzack, Sandro (Proceedings of the Design Society, 2023)
With increasing life expectancy, the risk of diseases of the central nervous system, such as cancer,strokes, etc., also increases. Strokes often result in injury to the sciatic nerve, which is responsible forcontrolling the calf muscles (plantar and dorsal flexors). A so-called ankle joint orthosis (AFO) helps tosupport the pathological gait and to avoid foot drop during gait. Passive orthoses are of particularimportance for research, as they do not require additional incoming energy from outside to the orthoticsystem. However, current passive orthoses are often not personalized. On the one hand, because theyusually have only a temporary muscle-building function and, on the other hand, because the individualdesign process is computationally time consuming and thus expensive. This paper presents a possibilityto pre-dimension and pre-design passive orthoses fast and cost-efficiently by reducing the complexityof the model based on volume-optimized truss elements. Therefor a traditional high calculation intensivedesign procedure is compared with the complexity reduced model to show its effectiviness and thesimilarity of the results. Witl incoming energy from outside to the orthoticsystem. However, current passive orthoses are often not personalized. On the one hand, because theyusually have only a temporary muscle-building function and, on the other hand, because the individualdesign process is computationally time consuming and thus expensive. This paper presents a possibilityto pre-dimension and pre-design passive orthoses fast and cost-efficiently by reducing the complexityof the model based on volume-optimized truss elements. Therefor a traditional high calculation intensivedesign procedure is compared with the complexity reduced model to show its effectiviness and thesimilarity of the results. <br
Keywords: Orthoses; User centred design; Lightweight design; Truss optimization; Design methods